2016
DOI: 10.1039/c5ta07443f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically generated sol–gel films as inhibitor containers of superhydrophobic surfaces for the active corrosion protection of metals

Abstract: The present work shows a new contribution to the design of superhydrophobic surfaces with the additional function of active corrosion protection, through the encapsulation of inhibiting agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…Films based on TE-OS/DTMS electrodeposited on AA2024-T3 alloy in the presence of cerium nitrate were studied by Zhang et. al [16]. Through the water contact angle analysis, the authors observed angles near to 160º indicating the formation of superhydrofobic surfaces, which remains unchanged with the introduction of cerium.…”
Section: Introducionmentioning
confidence: 94%
“…Films based on TE-OS/DTMS electrodeposited on AA2024-T3 alloy in the presence of cerium nitrate were studied by Zhang et. al [16]. Through the water contact angle analysis, the authors observed angles near to 160º indicating the formation of superhydrofobic surfaces, which remains unchanged with the introduction of cerium.…”
Section: Introducionmentioning
confidence: 94%
“…When damage occurs, the corrosion inhibitors leach out and form barrier films by chemical complexation or physical adsorption on the exposed substrates [38][39][40] . A few recent studies have incorporated corrosion inhibitors to superhydrophobic coatings [41][42][43] . For example, Zhang et al recently prepared cerium nitrate or BTA-containing superhydrophobic films on aluminum alloy via the electro-assisted deposition of silica microparticles 41 .…”
Section: Introductionmentioning
confidence: 99%
“…A few recent studies have incorporated corrosion inhibitors to superhydrophobic coatings [41][42][43] . For example, Zhang et al recently prepared cerium nitrate or BTA-containing superhydrophobic films on aluminum alloy via the electro-assisted deposition of silica microparticles 41 . Results obtained using the scanning vibrating electrode technique (SVET) revealed that the corrosion activity in the scratched area could be effectively suppressed by the corrosion inhibitors, thereby exerting a self-healing corrosion inhibition effect.…”
Section: Introductionmentioning
confidence: 99%
“…contact angle (CA) and a maximum 10°. sliding angle (SA) for water droplets have attracted extensive attention due to their great significance in both fundamental research and potential applications in the fields of oilwater separation [1][2][3][4], water collection [5], anti-fogging [6], antiicing [7], energy conversation [8], self-cleaning [9,10], anti-corrosion [11,12], and friction drag reduction [13], etc. In general, there are two key points to equip surfaces with superhydrophobicity: creating a suitable surface roughness with micro-nanoscale hierarchical structures and low surface energy material modifications, which derived from the phenomenon of superhydrophobicity in nature [14,15].…”
Section: Introductionmentioning
confidence: 99%